2006
DOI: 10.1111/j.1365-2141.2005.05909.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards targeted therapy for infant acute lymphoblastic leukaemia

Abstract: SummaryDespite the greatly improved treatment regimes for childhood acute lymphoblastic leukaemia (ALL) in general, resulting in long-term survival in approximately 80% of cases, current therapies still fail in >50% of ALL cases diagnosed within the first year of life (i.e. in infants). Therefore, more adequate treatment strategies are urgently needed to also improve the prognosis for these very young patients with ALL. Here we review the current acquaintance with the biology of infant ALL and describe how thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 125 publications
2
44
1
3
Order By: Relevance
“…Our results could have been affected by the preferential participation of surviving cases if the factors under study affect prognosis. However, none of the variables investigated here has been associated with survival (4,5). In addition, because proxy interview was the object of data collection, deceased cases were eligible for the study; 27% of cases were not living at the time of maternal interview.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results could have been affected by the preferential participation of surviving cases if the factors under study affect prognosis. However, none of the variables investigated here has been associated with survival (4,5). In addition, because proxy interview was the object of data collection, deceased cases were eligible for the study; 27% of cases were not living at the time of maternal interview.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year survival rate for infant leukemia of f45% is considerably lower than that for leukemia at older ages (3). Presence of an MLL rearrangement is an important predictor of survival for infants with acute lymphoblastic leukemia (ALL); in a recent review, event-free survival was <15% and >50% among MLL + and MLL À cases, respectively (4). The prognostic importance of MLL rearrangements in infant acute myelogenous leukemia (AML) is less clear (5).…”
Section: Introductionmentioning
confidence: 99%
“…New therapeutic targets have to be identified by unraveling the biology of MLL-rearranged ALL. Phase 1/2 trials with FLT3 inhibitors 20 are currently being initiated in infant MLL-rearranged ALL.…”
Section: Org Frommentioning
confidence: 99%
“…www.bjournal.com.br considering the MLL translocation to be the first genetic hit undoubtedly arising in utero, but yet displaying N region-positive DJ H junctions, it is very likely that an exquisitely short latency period for only limited mutagenic events is further required (14,32). Furthermore, it was recently found that the receptor tyrosine kinase FLT3 is highly expressed in MLL-rearranged ALL as compared with other leukemias (6).…”
Section: Other Molecular Markersmentioning
confidence: 99%